Trauerfeier. Parkfriedhof in Bln.Lichterfelde. Dritte Reihe von Links: H. Müller, Paul Löbe und Carl Severing
Trauerfeier. Parkfriedhof in Bln.Lichterfelde. Dritte Reihe von Links: H. Müller, Paul Löbe und Carl Severing.